(untitled) (Research, Society and Development, 2021)
In Goiás, seasonal forests structure studies are scarce, especially in fragments located in legal reserves, subject to human disturbances. Therefore, the study aimed to perform the phytosociology of a fragment of a rural property, in a seasonal semideciduous forest. We evaluated structure, richness, diversity, dispersion mechanisms, ecological groups, and species distribution patterns found in the study and floristic links between Cerrado, Amazon and Atlantic Forest. In a one-hectare sample plot, all live trees with a diameter at breast height ≥ 10 cm were measured. The values of density and basal area were 561 ind.ha-1 and 26.2 m².ha-1, respectively. We recorded 37 species with diversity indices (H’) of 2.36 and evenness (J’) of 0.65. Toulicia reticulata, Chaetocarpus echinocarpus, Bocageopsis mattogrossensis and Nectandra cuspidata were species with the highest importance value, corresponding to 69% and 65% of all density and basal area, respectively. Fabaceae obtained the highest floristic richness, with six species, although it was little represented in terms of abundance. Our results suggest that the fragment is a mature forest in good conservation status. This is reinforced by the high size of trees, in addition to the predominance of zoochoric (83.8%) and secondary (92.1%) individuals in the survey.